Fluid-structure interaction modelling of blood flow in peripheral arterial disease - Muhammad Firdaus, Mohd Fauzi; Nasrul Hadi, Johari; Mohd Jamil, Mohamed Mokhtarudin; Bazli, Mohd Yusoff; Guo, Baolei (Semarak Ilmu Publishing, 2024)
The study presents the fluid-structure interaction (FSI) modeling in Peripheral Arterial Disease (PAD) geometry, highlighting the effects of arterial blockage on hemodynamics and arterial wall mechanics. Employing a RANS-based SST-Tran model, the study examines stenotic PAD models under realistic boundary conditions, coupled with a hyperelastic Mooney-Rivlin model to simulate the arterial wall's response. The analysis includes velocity profiles, wall shear stress (WSS), pressure distribution, and wall displacement, revealing significant differences between healthy and stenosed models. It demonstrates adaptive hemodynamics, the impact of stenosis on flow mechanics, and potential implications for atherosclerosis and plaque formation. The findings highlight the importance of understanding stenosis severity for clinical risk assessment, treatment planning, and monitoring.